2021
DOI: 10.1161/strokeaha.120.032130
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-Lymphocyte Ratio Predicts Cerebral Edema and Clinical Worsening Early After Reperfusion Therapy in Stroke

Abstract: Background and Purpose: The mechanisms linking systemic inflammation to poor outcome in ischemic stroke are not fully understood. The authors investigated if peripheral inflammation following reperfusion therapy leads to an increase in cerebral edema (CED), thus hindering the clinical recovery. Methods: We designed a single-center study conducted at Centro Hospitalar Universitário São João between 2017 and 2019. Inclusion criteria were being adult, havi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
74
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(87 citation statements)
references
References 27 publications
9
74
4
Order By: Relevance
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…Various studies have shown that NLR is closely related to AIS dysfunction, short-term mortality, stroke severity on admission, primary unfavorable functional outcome, recurrent ischemic stroke and post stroke infections, greater risk of symptomatic intracranial hemorrhage, poor 3-month functional outcome, and 3-month mortality in AIS patients undergoing reperfusion treatments, which is consistent with our results (Xue et al, 2017;Kocaturk et al, 2019;Chen et al, 2020;Giede-Jeppe et al, 2020;He et al, 2020;AltinbaŞ et al, 2021;Bi et al, 2021;Ferro et al, 2021;Gong et al, 2021;Hu et al, 2021;Huang et al, 2021;Lin et al, 2021). In a recent study, NLR ≥ 9 was an independent predictor of new in-hospital neurologic complications (Heuschmann et al, 2004).…”
Section: Discussionsupporting
confidence: 92%
“…A number of studies have shown that NLR was predictive of short-term functional outcome in acute ischemic stroke (AIS) (116). A high NLR was also found to be an independent predictor for the complications following AIS including cerebral edema (117), hemorrhagic transformation after ischemia (118), and the development of ICH after endovascular treatment (119).…”
Section: Other Roles Of the Nlr And Implications For Future Researchmentioning
confidence: 99%
“…Reasons for this finding may be the small cohort size. According to recently published data, NLR represents a promising marker in stroke for the prediction of symptomatic hemorrhagic transformation (sHT) undergoing revascularization 45 and cerebral edema after reperfusion therapy 46 .…”
Section: Discussionmentioning
confidence: 99%